The role of BRCA status on the prognosis of patients with epithelial ovarian cancer: a systematic review of the literature with a meta-analysis. - Chaoyang Sun; Na Li; Dong Ding; Danhui Weng; Li Meng; Gang Chen; Ding Ma (PLoS ONE, 2014)
Objective The role of BRCA dysfunction on the prognosis of patients with epithelial ovarian cancer (EOCs) remains controversial. This systematic review tried to assess the role of BRCA dysfunction, including BRCA1/2 germline, somatic mutations, low BRCA1 protein/mRNA expression or BRCA1 promoter methylation, as prognostic factor in EOCs. Methods Studies were selected for analysis if they provided an independent assessment of BRCA status and prognosis in EOC. To make it possible to aggregate survival results of the published studies, their methodology was assessed using a modified quality scale. Results Of 35 evaluable studies, 23 identified BRCA dysfucntion status as a favourable prognostic factor. No significant differences were detected in the global score of quality assessment. The aggregated hazard ratio (HR) of overall survival (OS) of 34 evaluable studies suggested that BRCA dysfunction status had a favourable impact on OS (HR = 0.69, 95% CI 0.61-0.79), and when these studies were categorised into BRCA1/2 mutation and low protein/mRNA expression of BRCA1 subgroups, all of them demonstrated positive results (HR = 0.67, 95% CI: 0.57-0.78; HR = 0.62, 95% CI: 0.51-0.75; and HR = 0.51, 95% CI: 0.33-0.78, respectively), except for the subgroup of BRCA1 promoter methylation (HR = 1.59, 95% CI: 0.72-3.50). The meta-analysis of progression-free survival (PFS), which included 18 evaluable studies, demonstrated that BRCA dysfunction status was associated with a longer PFS in EOC (HR = 0.69, 95% CI: 0.63-0.76). Conclusions Patients with BRCA dysfunction status tend to have a better outcome, but further prospective clinical studies comparing the different BRCA statuses in EOC is urgently needed to specifically define the most effective treatment for the separate patient groups.